Study of Association of Dietary Factors with Severity of Acute Pancreatitis - Aliza Abidi, Hazrat Bilal, Shazadi Neelum Agha, Danyal Zahoor, Ghulam Shabbir, Imam Baksh, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the association of dietary factors with severity of acute pancreatitis (AP). Materials and Methods: A total of 250 patients who presented in General Surgery unit from Jan-2022 to Dec-2022 were included. Data regarding etiology of AP and demographics of patients was obtained. A special questionnaire was designed to obtain information regarding the dietary habits of patients based on different types of diet. The questionnaire included information regarding use of meat, fat in daily diet, dairy products use, and desserts use. Results: Mean age of study patients was 48.3±18.5 years. Majority were females, 135 (54%) were females and 115 (46%) were males. There was significant association of meat rich diet and fat rich diet with severity of AP, 81 (60.9%) patients of mild AP had main diet as meat, 47 (68.1%) in moderate AP group and 40 (83.3%) in severe AP group had main diet as meat (p-value 0.01). 15 (11.3%) patients in mild AP, 11 (15.9%) in moderate AP and 13 (27.1%) in severe AP group reported to have use high fat usage in daily diet (p-value 0.03). Conclusion: Meat rich and fat rich diets are independently associated with severe AP. So modification of diet in-terms of reduction in meat and fat and addition of fibrous food in daily diet can help to reduce in incidence and severity of AP in high risk patients. Keywords: Acute Pancreatitis, dietary factors, disease severity, meat, fat